(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2021)
BACKGROUND: α2 agonists are first approved by FDA for only sedation in ICU. But at present they are explored in various surgeries and in various routes. In present study we evaluate efficacy of Clonidine and Dexmedetomidine in neuro anaesthesia for transsphenoidal removal of pituitary adenomas. AIMS & OBJECTIVES: To evaluate efficacy of Clonidine and Dexmedetomidine in neuro anaesthesia for premedication, induction, haemodynamic stability, post operative smooth extubation, recovery profile. STUDY DESIGN: Randomised double blind observation study. MATERIAL & METHODS: present study was done in V.S. general hospital & SVP hospital, N.H.L. municipal medical college, Ahmedabad in neurosurgery & Anaesthesia during 2015-2019. Adult 80 patients for elective surgery for pituitary adenoma transsphenoidal Removal patients grade 1 or 2 enrolled in study and they are randomly allocated to2 groups. Randomisation done by odd& even number in seal opaque envelope. execution of randomisation at time of giving general anaesthesia. In group C: patients had received Inj. Clonidine pre operatively 1 mcg/kg loading dose over 10 min by infusion pump followed by 0.5 mcg/kg/hr after intubation. In group D: patients had received Inj. Dexmeditomidine pre operatively 1 mcg/kg loading dose over 10 min by infusion pump followed by maintenance infusion 0.5 mcg/kg/hr after intubation. Patients are induced with Propofol 2 mg/kg and Inj. Atracurium 0.5 mg/kg and intubated with appropriate size endotracheal tube and maintained with O2, N2O, sevoflurane (0.2-0.5 MAC) in close circuit and Inj. Vecuronium bromide on Drager Fabius GS Work Station. In both the group infusion of drug was continued till dura closure by infusion pump. OBSERVATION & RESULTS: In both the groups patients had stable haemodynamics and smooth post operative recovery and extubation. Rate of reintubation was very less in both the groups. CONCLUSION: α 2 agonists are good adjuvants for Transsphenoidal pituitary adenoma removal. Dexmeditomidine is better than Clonidine in Transsphenoidal pituitary adenoma removal.